PROPAEDEUTICS OF STUDYING QUANTUM COMPUTER SCIENCE IN A SPECIALIZED (HIGH) SCHOOL - Lehka, L.; Shokaliuk, S.; Bohunenko , E. (Physical and Mathematical Education, 2021)
The article offers experimental models for studying the basics of quantum computer science in specialized (high) schools with key methodological recommendations for their implementation in the educational process. Formulation of the problem. The current role of school informatics is based on the study of digital technologies, which are focused on working with computers of exclusively classical architecture, while are gaining more and more practical importance in various spheres new technologies - quantum technologies. Notwithstanding the complex nature of quantum technologies, but taking into account their perspectives, there is a need to start learning the basics of new quantum informatics in the lessons of specialized (high) schools in the form of educational material, adapted to the age specifics of high school children. Materials and methods. To obtain the results, we used theoretical methods of scientific search – analysis of scientific sources on quantum computer science and methods of teaching computer science at institutions of general secondary education and synthesis of components of the methodology for teaching the basics of quantum computer science. Results. At this stage of research, three experimental models of propaedeutic study of quantum computer science are proposed for implementation in the educational process of specialized (high) schools: 1) the model Selective module “The fundamentals of quantum computer science”; 2) the model Through study of the basics of quantum computer science in Physics, Mathematics and Computer science courses; 3) the model Integrated course “ The fundamentals of quantum computer science”. Conclusions. The inclusion of quantum computer science issues adapted for perception and assimilation by high school students in the content of academic subjects in the natural-mathematical and technological educational fields today will increase a motivation to learn through the practical significance of their updated content.